An Analysis of The Role of Village-Owned Enterprises (Bumdes) in Boosting The Economy of The Village Community and Village-Generated Revenue (Pades) in Kedakas Village, Tayan Hulu Subdistrict, Sanggau Regency - Marga Suryadi; Syamsuri Syamsuri (Journal of Social Research, 2026)
This study aims to analyze the role of Village-Owned Enterprises (Badan Usaha Milik Desa/BUMDes) in improving the community's economy and Village Original Income (Pendapatan Asli Desa/PADes) in Kedakas Village, Tayan Hulu District, Sanggau Regency. This research is motivated by the suboptimal management of village potential, which has resulted in limited contributions to PADes and community welfare. The method used is a qualitative approach with data collection techniques comprising interviews, observations, and documentation, with informants consisting of the village head, BUMDes managers, village officials, and community members. The results of the study show that BUMDes have operated several business units, including oil palm fresh fruit bunch management, rental services, and food security enterprises, which have had a positive impact on the community's economy, particularly for those directly involved. BUMDes have also contributed to PADes, although these contributions remain limited. The principles of transparency, accountability, participation, and professionalism have begun to be implemented, but have not yet been applied optimally. Supporting factors include village government support, community participation, and available village potential, while inhibiting factors include limited capital, low human resource capacity, and business competition. It is concluded that BUMDes play an important role, but still require more optimal management so that the benefits can be felt more broadly and sustainably.